Agronegócio versus agricultura familiar: a dinâmica da ocupação do espaço no município de Chapadinha/MA, a partir dos anos de 1990 - FEITOZA, Ilnar Fernandes (2018)
This dissertation analyzes the occupation of space in the municipality of Chapadinha, from the 1990s, with the objective of investigating the impacts caused by the advance of agribusiness on family agriculture, in the logic of capitalist expansion to the countryside. Initially the theoretical and methodological references are explained, in which the theories about the advance of capitalism for agriculture are highlighted, being the first as general discussion of the classic authors and the last, as a contextualized discussion in the Brazilian reality. From the indicated references, we analyze the bases of the expansion of capitalism for agriculture and the dynamics of the advance, especially in Brazilian agriculture, in the current neoliberal phase of capitalism, as well as the State's performance in this process. Then, taking the municipality of Chapadinha in the state of Maranhão as an empirical reference, the impacts of the advance of capitalism to the countryside are clarified by means of public incentives that corroborated the expansion of monocultures in Maranhão. Following, the main socioeconomic indicators of Brazil, Maranhão and Chapadinha, 1991, 2000 and 2010, and the participation of the agricultural sector are analyzed. Finally, the impact of the expansion of soybean and eucalyptus monocultures in Chapadinha / MA, as well as the social and economic impacts for those who depend on small spaces to produce, are discussed. Based on the surveys, it was concluded that the expansion of monocultures to Chapadinha has had considerable negative impacts on small-scale agriculture, as well as a combination of social, economic and environmental damage to the residents and the village ecosystem. It is concluded that in Chapadinha, agribusiness advances by taking over the spaces, compressing family farming and the old ways of producing and living of small producers.